2000
DOI: 10.1080/02664760021673
|View full text |Cite
|
Sign up to set email alerts
|

Zero-inflated proportion data models applied to a biological control assay

Abstract: Biological control of pests is an important branch of entomology, providing environmentally friendly forms of crop protection. Bioassays are used to find the optimal conditions for the production of parasites and strategies for application in the field. In some of these assays, proportions are measured and, often, these data have an inflated number of zeros. In this work, six models will be applied to data sets obtained from biological control assays for Diatraea saccharalis , a common pest in sugar cane produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 0 publications
0
59
0
2
Order By: Relevance
“…Recently, in many fields, it has become popular to model such data using regression models based on an assumption that the response is generated by a mixture of a standard count distribution (e.g. binomial, Poisson, or negative binomial) with a degenerate distribution with point mass of one at zero, creating a zero-inflated distribution (Hall 2000;Vieira et al 2000). As mentioned earlier, Martin et al (2005) reports that there are currently no reported models in the literature for data with zero-inflation due to both true and false zeros, and the use of mixture models based ZIP or ZINB distributional assumptions may not account for "false zeros" when modeling the data.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in many fields, it has become popular to model such data using regression models based on an assumption that the response is generated by a mixture of a standard count distribution (e.g. binomial, Poisson, or negative binomial) with a degenerate distribution with point mass of one at zero, creating a zero-inflated distribution (Hall 2000;Vieira et al 2000). As mentioned earlier, Martin et al (2005) reports that there are currently no reported models in the literature for data with zero-inflation due to both true and false zeros, and the use of mixture models based ZIP or ZINB distributional assumptions may not account for "false zeros" when modeling the data.…”
Section: Introductionmentioning
confidence: 99%
“…Proportional data were modeled with a binomial distribution and logit link function. Overdispersion, which is common with proportional data in binomial models and can lead to underestimates of standard error, was corrected with the addition of a dispersion parameter ø that is equal to Pearson χ 2 / df estimated from the global model (Vieira et al 2000). In our global model, Pearson χ 2 / df = 4.346, suggesting overdispersed data; therefore, 4.346 was used as an estimate of ø in all models and ĉ for quasi-likelihood adjusted Akaike's information criteria (QAIC c ) calculations.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review and a discussion on a general methodology to model zero inflated count data is presented in Ridout et al (1998), with emphasis in applications in horticulture. Some models for zero inflated data of proportions with applications to biological control assays are also presented in Vieira et al (2000). Other recent applications of non spatial Poisson and binomial zero inflated models can be found for instance in Hall (2000) and in a Bayesian context in Angers & Biswas (2003); Rodrigues (2003) and Ghosh et al (2006).…”
Section: Spatio-temporal Statistical Modelsmentioning
confidence: 99%